The gay book of days : an evocatively illustrated who's who of who is, was, may have been, probably was, and almost certainly seems to have been gay during the past 5,000 years - Greif, Martin, 1938-1996 (Secaucus, N.J. : L. Stuart, 1982)
Wie is wie in de homowereld?
"A Main Street Press book."
Includes index.
Bibliography: p. 219.
Keywords: Birthday books; Gay people -- Biography